Inhibition of trehalose synthesis in lepidoptera reduces larval fitness - Tellis, Meenakshi B.; Mohite, Sharada D.; Nair, Vineetkumar S.; Chaudhari, Bhagyashri Y.; Ahmed, Shadab; Kotkar, Hemlata M.; Joshi, Rakesh S. (Advanced Biology, 2024)
Trehalose is synthesized in insects through the trehalose 6-phosphate synthase and phosphatase (TPS/TPP) pathway. TPP dephosphorylates trehalose 6-phosphate to release trehalose. Trehalose is involved in metamorphosis, but its relation with body weight, size, and developmental timing is unexplored. The expression and activity of TPS/TPP fluctuate depending on trehalose demand. Thus, TPS/TPP inhibition can highlight the significance of trehalose in insect physiology. TPS/TPP transcript levels are elevated in the pre-pupal and pupal stages in Helicoverpa armigera. The inhibition of recombinantly expressed TPP by N-(phenylthio)phthalimide (NPP), is validated by in vitro assays. In vivo inhibition of trehalose synthesis reduces larval weight and size, hampers metamorphosis, and reduces its overall fitness. Insufficient trehalose leads to a shift in glucose flux, reduced energy, and dysregulated fatty acid oxidation. Metabolomics reaffirms the depletion of trehalose, glucose, glucose 6-phosphate, and suppressed tricarboxylic acid cycle. Reduced trehalose hampers the energy level affecting larval vitality. Through trehalose synthesis inhibition, the importance of trehalose in insect physiology and development is investigated. Also, in two other lepidopterans, TPP inhibition impedes physiology and survival. NPP is also found to be effective as an insecticidal formulation. Overall, trehalose levels affect the larval size, weight, and metabolic homeostasis for larval-pupal transition in lepidoptera. Inhibition of trehalose synthesis enzyme TPS/TPP is a good model to study the contribution of trehalose in attaining body weight and in larval-pupal transition. Transcriptomics and metabolomics studies reveal overall reduced energy and dysregulated glucose, protein, and fatty acid metabolism.image
Keywords: Lepidoptera; metabolic homeostasis; trehalose; trehalose 6-phosphate phosphatase